THE EFFECT OF USING TOP-DOWN PROCESSING APPROACH ON READING COMPREHENSION ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 40 PEKANBARU - Husna, Maulida; ', Afrianto; ', Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed at finding out if there is any effect of using Top-Down Processing approach on reading comprehension ability of the second year students of SMPN 40 Pekanbaru. This study was a pre-experimental research. The researcher used one group pre-test post-test design to distinguish the effect of using top-down processing approach between the pre-test and the post-test results. The total population in this study was 165 students from four classes. To choose the sample the researcher used cluster random sampling technique. Class VIII.C with 40 students was chosen as the sample. The instrument used to get the data is an objective test. The form of text in the test is narrative text. The test consists of 4 narrative texts with 20 objective questions. Each text has 5 multiple choice type of questions. The researcher used t-test by employing SPSS (Statistical Product and Service Solutions) statistics version 17.0 to measure and compare the students’ scores in reading comprehension between the pre-test and the post-test results. The post-test result (79.75) was higher than the pre-test result (61.12). The correlation coefficient between the pre-test and post-test results is 0.868 which indicates that it has a strong correlation. The result indicates that using top-down processing approach is effective to improve the students’ reading comprehension ability.Key Words: Effects, top-down processing approach, reading comprehension